(untitled) (Andamios, Revista de Investigación Social, 2012)
In this paper, by revisiting the Lynch-Bloor debate (1992) and from a re-interpretation of the article “Understanding a Primitive Society” (1964) by Peter Winch, I will argue that from the demythologization of knowledge processes carried out in the past decades a positive proposal follows. This proposal consists in a critical approach, which allows social studies of science and technology to transcend its attachments to a mere descriptive view of knowledge. This opens up the possibility that even when we accept that epistemic practices are culture dependent there is still the possibility to evaluate them in the light of “other cultures”.